The Skill of Speed: Insights from world-class sprint coaches on the development of sprinting technique - Mason, J.; Zech, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Periodisation frameworks in individual sports describe the organisation of training to achieve physiological adaptations which drive improvements in key qualities such as strength, power and endurance. Few frameworks address the organisation of training for the acquisition of technique and skill, particularly in track and field. Therefore, the purpose of this research project was to elicit insights into the practices and perspectives of world class coaches regarding training design for the development of technique in sprinters. METHODS: A qualitative research design was employed using semi-structured interviews. Seven elite sprint coaches were recruited. To be eligible, coaches must have coached at least one sprint athlete to qualification for a major international championship. Questions related to micro and macro aspects of training designed to develop and refine sprint technique. Inductive thematic analysis was used to analyse the interview transcripts (Braun & Clarke 2006). RESULTS: Emergent themes indicate that coaches commonly manipulate constraints to develop and refine sprint technique, including the use of sprint drills. All coaches deliberately target elements of sprinting technique multiple times per week during both preparation and competition cycles, although the temporal organisation and progression of this dedicated practice over time differs. Progressions in skill training are typically represented by increases in intensity or complexity. Multiple coaches articulated difficulties creating robust changes in technique which transfer to race performance. While coaches identified common objectives for different sprinting skills, some emphasized that there is no single model that they orient their athletes towards and instead combine their understanding of biomechanics with the unique characteristics of each individual to inform areas of focus and the subsequent prescription of training. Overall, coaches rely largely on experiential knowledge when prescribing technical training, and strategies to monitor and evaluate the outcomes of this training are varied and sometimes absent. CONCLUSION: These insights reveal common approaches shared by elite sprint coaches regarding skill acquisition in sprinting, highlight the complexities of refining sprint technique and indicate an absence of clear framework for progressing technical training over time. This demonstrates a need for coaches to have a strong understanding of the general biomechanical features underpinning sprint performance to appropriately identify the needs of the athlete and subsequently accommodate and exploit their organismic constraints. Future research should build on traditional skill acquisition research to design ecologically valid models for the development of sprinting technique to maximise the transfer of training to race day.